1999
DOI: 10.1080/00074919912331337697
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Vulnerability to Financial Crisis: Evidence from Indonesia

Abstract: This paper examines the view that the recent Indonesian crisis was largely unforeseen. The broadest macroeconomic indicators were of virtually no help in presaging the crisis; neither were high-frequency financial indicators. But warnings were there, just below the surface, in some of the macro indicators and in certain structural weaknesses that were long recognised as threats to financial stability. That said, none of these warnings suggested crisis of the magnitude that eventually occurred. The Indonesian e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…These results are consistent with the analysis of the weakness of the Korean banking system and deteriorating fundamentals as laying the basis for its crisis (Puri et al, 2002). Analysis of the turmoil in Indonesian financial markets during the East Asian crisis generally highlights the role of political unrest, but disagrees on the extent of fundamental problems; Kenward (1999) argues that Indonesian fundamentals were sound, while Iriana and Sjöholm (2002) point to the role of the larger share of short-term debts as a weakness. Owing to this 112 M. DUNGEY AND V. L. MARTIN relative perceived fundamental strength, Radelet and Sachs (1998) and Goldstein et al (2000) have suggested that Indonesia was the country most affected by contagion in this crisis.…”
Section: Variance Decompositionssupporting
confidence: 79%
“…These results are consistent with the analysis of the weakness of the Korean banking system and deteriorating fundamentals as laying the basis for its crisis (Puri et al, 2002). Analysis of the turmoil in Indonesian financial markets during the East Asian crisis generally highlights the role of political unrest, but disagrees on the extent of fundamental problems; Kenward (1999) argues that Indonesian fundamentals were sound, while Iriana and Sjöholm (2002) point to the role of the larger share of short-term debts as a weakness. Owing to this 112 M. DUNGEY AND V. L. MARTIN relative perceived fundamental strength, Radelet and Sachs (1998) and Goldstein et al (2000) have suggested that Indonesia was the country most affected by contagion in this crisis.…”
Section: Variance Decompositionssupporting
confidence: 79%
“…Its' openness and export growth are only slightly higher than those of Indonesia, which is clearly the worst performing country in the sample on the basis of these indicators. Note that Kenward (1999) describes the lack of macroeconomic indicators of weakness in Indonesia prior to the crisis and Iriana and Sjöholm (2002) find less evidence of weakness than other economies in the region, but point to the role of the larger share of short term debts.…”
Section: Strong Fundamentals Imply Immunity To Contagionmentioning
confidence: 99%
“…2 A number of previous studies suggested that the Indonesian crisis could not be explained by macroeconomic imbalances alone. See, for instance, McLeod (1997), Furman and Stiglitz (1998), Radelet and Sachs (1998), Kenward (1999), and Hill (2000). across countries and often manifests itself as a comovement of, for instance, exchange rates and stock prices.…”
Section: Introductionmentioning
confidence: 99%